DESIGN IMPROVEMENT OF A LIQUID-MODERATOR-BASED NEUTRON SPECTROMETER FOR BNCT. Issue 1 (27th October 2017) - Tamaki, Shingo; Kusaka, Sachie; Sato, Fuminobu; Murata, Isao
Abstract: Boron neutron capture therapy is known to be an effective radiation cancer therapy that requires neutron irradiation. A neutron field generated by an accelerator-based neutron source has various energy spectra, and it is necessary to evaluate the neutron spectrum in the treatment field. However, the method used to measure the neutron spectrum in the treatment field is not well established. Many researchers are making efforts to improve the spectrometers. To solve this problem, we are developing a liquid-moderator-based neutron spectrometer that is based on the same theory as that of the Bonner sphere spectrometer. The spectrometer uses a liquid moderator and absorber. In the present study, we performed a design study to improve the previously developed liquid-moderator-based neutron spectrometer. By carrying out a numerical simulation of the designed new spectrometer, we finally assessed and confirmed the validity of this spectrometer numerically.